2020
DOI: 10.11604/pamj.2020.37.60.22848
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of folic acid among women of childbearing age in Benue State, Nigeria

Abstract: Introduction every year in Nigeria 12,695 babies are born with neural tube defects. Folic acid reduces the risk of neural tube defect by about 50% among peri-conceptional users. We conducted this study to determine the awareness and use of folic acid among women of childbearing age in Benue State, Nigeria. Methods we conducted a cross-sectional study among women attending selected among six secondary health facilities in Benue State using a multi-stage sampling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
5
7
2
2
Order By: Relevance
“…However, they didn't specify what kind of birth defects FA prevents. Similarly, a study done in Nigeria showed that 25.9% were aware that FA hindered the development of NTDs [27]. Similar results were obtained from research done in Ha'il in 2013, which revealed that 81% of women knew that FA has a role in preventing NTDs [5].…”
Section: Discussionsupporting
confidence: 66%
“…However, they didn't specify what kind of birth defects FA prevents. Similarly, a study done in Nigeria showed that 25.9% were aware that FA hindered the development of NTDs [27]. Similar results were obtained from research done in Ha'il in 2013, which revealed that 81% of women knew that FA has a role in preventing NTDs [5].…”
Section: Discussionsupporting
confidence: 66%
“…A survey conducted in Korea showed that 65.6% of surveyed women had heard of FA before pregnancy, and 26.4% reported on the pre-conceptional use of FA [ 9 ]. 9 In some other studies, the knowledge regarding FA need varied from 34.0% to over 67% [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, despite their knowledge, few women, as low as 9.4% in some studies to as much as 46.3% in others, in their childbearing age take FA supplements [ 11 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 In some other studies, the knowledge regarding FA need varied from 34.0% to over 67% [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, despite their knowledge, few women, as low as 9.4% in some studies to as much as 46.3% in others, in their childbearing age take FA supplements [ 11 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations